Digital innovations in the post-pandemic era towards safer and sustainable food operations: A mini-review - Halim-Lim, Sarina Abdul; Baharuddin, Azan Azuwan; Cherrafi, Anass; Ilham, Zul; Jamaludin, Adi Ainurzaman; David, Wahyudi; Sodhi, Harsimran Singh (Frontiers in Food Science and Technology, 2023)
Though the pandemic has created an imbalance and disrupted the economy in the food industry, it has had a positive impact on speeding the acceptance of the industry towards digital innovations (DI). The shift toward digitalization is leading the food industry to leverage innovations that can serve the dual purpose of safer and sustainable food operations. This review synthesizes the rapidly growing literature on digital technology used as the response to the emergence of food safety and sustainability issues during the COVID-19 pandemic. Opportunities to improve thirteen food safety management system components and three sustainability components including economics, environmental and social were identified. The review determined that blockchain and IoT have the most prominent role in improving food safety, especially the component of traceability and monitoring and inspection.